Peningkatan Keterampilan Berbicara Bahasa Jawa Krama Melalui Model Pembelajaran Role Playing Pada Siswa Menengah Pertama - Handayani, Lina; Mulyana, Mulyana (Universitas Cokroaminoto Palopo, 2024)
Communicating using unggah-ungguh basa Jawa or correct Javanese speech acts is currently one of the obstacles for students in the Java area, especially class VII students at SMP 4 Kudus. This is proven by the low average score on the Javanese pacelathon material. Based on these observations, it is necessary to apply the role playing learning model to improve polite Javanese speaking skills in the language unggah-ungguh basa Jawa speaking material. The aim of this research is to improve Javanese Krama speaking skills through role playing models. The results of the research show that learning outcomes in the unggah-ungguh basa Jawa speaking material have increased in the sufficient category, which was originally 46%, experiencing an increase of 64% in cycle 2, which means that in cycle II there were no students in the sufficient category. Furthermore, for the less than 14% category, in cycle 2 it increased to 86%. In cycle II, it showed that 100% of students were in the good (57%) and very good (43%) categories. The conclusion is that after studying with the role playing learning model, class VII A students originally had a class average score of 73.6, after implementing the role playing model it became 88.5. The conclusion of this research is that the role playing learning model improves Javanese Krama speaking skills.